Strategi Pemasaran Sayuran di Perusahaan Pacet Segar Cianjur - Yeni Kusumaway; Tengku Harunur Rasyid (Jurnal Sagu, 2009)
This research was a case study of pacet segar, a vegetable wholesaler in Cianjur, West Java, which aimed to: 1) assess its marketing strategies, 2) analyze its external and internal factors influencing those strategies, and 3) recommend alternative marketing strategies. Data were collected through observation, interview and literature stud. Data analysis included: 1) analysis of existing marketing strategies by describing the target market (segmentation, targeting and positioning) and the marketing mix (product, price, promotion and distribution), 2) analysis of internal and external factors by SWOT matrix to suggest alternative strategies. Identification, scoring and rating of the factors were based on interviews with company management. Research findings recommended that the company choose selective specialization target market in combination with risk spreading and service-based positioning. For the marketing mix, the company was suggestion to: 1) maintain product quality, 2) apply intensive distribution, 3) shorten the period of product price contract, and 4) increase affordable promotion.